PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR PERKALIAN DAN PEMBAGIAN PECAHAN DI KELAS V SEKOLAH DASAR - Chichi Mogi Sugini; Masniladevi Masniladevi (Universitas Negeri Padang, 2021)
This research aims to determine the effect of the Problem Based Learning model on learning outcomes in the material multipication and division of fraction in class V Elementary School. The research design used is Quasi Experimental Design. The population in this study were class V students of SDN 01 Maninjau . With the simple purposive sampling technique, the Va class was obtained as the experimental class and Vb as the control class. Based on the results of data analysis using t-test, obtained tcount = 3,8633 and ttable = 1.68595 at a significant level of 0.05 and dk = 38. It means tcount> ttable so that Ha is accepted. Therefore, there is a positive and significant effect on the Problem Based Learning learning model on learning outcomes in the material multiplication and division of fractions in class V Elementary School.